2021
DOI: 10.3390/ijms22136940
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 2 mRNA-Binding Protein 1 (IGF2BP1) Is a Prognostic Biomarker and Associated with Chemotherapy Responsiveness in Colorectal Cancer

Abstract: Insulin-like growth factor 2 mRNA-binding protein 1 (IGF2BP1) is an RNA-binding protein and serves as a post-transcriptional fine-tuner regulating the expression of mRNA targets. However, the clinicopathological roles of IGF2BP1 in colorectal cancer (CRC) remains limited. Thus, we aimed to elucidate the clinical significance and biomarker potentials of IGF2BP1 in CRC. A total of 266 specimens from two sets of CRC patients were collected. IGF2BP1 expression was studied by immunohistochemical (IHC) staining. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…The risk of colorectal cancer incidence significantly increases in carriers with the C allele in SNP rs6504593 located in IGF2BP1 (Insulin-Like Growth Factor-2 Binding Protein-1) [ 22 ]. Based on the literature, the expression level of IGF2BP1 in different types of cancer is changed [ 23 ]. Xie and colleagues indicated that miR-21 bound to SNP rs6504593 in IGF2BP1 could regulate the expression of IGF2BP1 and develop colorectal cancer risk.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of colorectal cancer incidence significantly increases in carriers with the C allele in SNP rs6504593 located in IGF2BP1 (Insulin-Like Growth Factor-2 Binding Protein-1) [ 22 ]. Based on the literature, the expression level of IGF2BP1 in different types of cancer is changed [ 23 ]. Xie and colleagues indicated that miR-21 bound to SNP rs6504593 in IGF2BP1 could regulate the expression of IGF2BP1 and develop colorectal cancer risk.…”
Section: Resultsmentioning
confidence: 99%
“…IGF2BP1 is a new member of the m 6 A-binding proteins; it is widely expressed in the process of embryonic development and is gradually downregulated after birth. Previous research has found that IGF2BP1 has more than 3,000 mRNA targets ( 22 , 27 , 31 , 32 ). By regulating the stability of target mRNA, IGF2BP1 plays important roles in regulating cell migration, cell proliferation, and cell metabolism and maintaining the epithelial phenotype ( 13 , 23 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IGF2BP1 is associated with poor prognosis of 13 organs including lung, esophagus, breast, thyroid, and kidney ( 27 , 32 , 37 , 38 ). Conversely, there are also a small number of studies demonstrating the tumor-protective roles of IGF2BP1 in gallbladder carcinoma, colitis-associated carcinoma, colorectal cancer, and breast carcinoma ( 39 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BP family consists of three members which exert negative effects in the late phase of embryo development; their expression is lost in adults and may be reactivated in tumors [ 181 , 182 ]. IGF2BP1 was evaluated as an independent prognostic marker in CRC associated with the responsiveness to chemotherapy [ 183 ]. Although IGF2BP expression is generally related to worse prognosis, opposing overall effects of different IGF2BP members in different cells were detected [ 48 ].…”
Section: Insulin-like Growth Factors and Colorectal Cancermentioning
confidence: 99%